EFFECTIVENESS OF PROPER NUTRITION IN GOUT - Xadjimetova Oygul Ikromovna (Web of Journals Publishing, 2024)
Gout is a common inflammatory arthritis characterized by the accumulation of uric acid crystals in the joints, which leads to severe pain and discomfort. This article explores the effects of proper nutrition on managing and preventing gout. The analysis shows that specific nutrition strategies can effectively lower uric acid levels, reduce flare-ups, and improve the health of people with gout.
Keywords: gout, diet, uric acid, diet management, inflammation, arthritis, health, lifestyle